KIE(Komunikasi Informasi dan Edukasi) tentang Pencegahan Covid-19 di Masa Kehamilan dan Persalinan pada Kelompok Ibu Hamil - Siti Asiyah Ahsanudin (STIKES dan AKZI Karya Husada Kediri, 2022)
Physiological and immunological changes that occur as a component of pregnancy can have systemic effects, and increase the risk of complications. Through evaluations carried out in previous coronavirus outbreaks (SARS and MERS), pregnant women have been shown to have a high risk of death, spontaneous miscarriage, premature birth. The fatality rate of SARS and MERS among pregnant patients was 25 percent and 40 percent, respectively, there are several risks such as premature rupture of membranes, premature birth, delivery of the fetus with serious conditions. But whether Covid-19 increases the risk of miscarriage and fetal death is not known for certain until now. Data regarding the number of pregnant women who are positive for Covid-19 in Indonesia is currently not clearly available. According to the Jakarta branch of the Indonesian Obstetrics and Gynecology Association (POGI), pregnant women have a 13.7 percent chance of being infected with Covid-19 compared to those who are not pregnant. The purpose of this bathing activity is to provide understanding and skills to pregnant women to do prevention and also to prepare for childbirth by observing health protocols. The method used in the service, cross-program collaboration with the Mojoangun Jombang Health Center and the Shafira Polindes, Merakurak District, Tuban Regency which is a partner in the clinical practice of the Professional Nurses Program STIKES Karya Husada Kediri, the total target of pregnant women is 85 pregnant women, Education is carried out directly or face to face with pregnant women with due observance of health protocols. Evaluation of the results using an understanding questionnaire before and after education. The knowledge of pregnant women before education was carried out about most of them there was 69 (81.17%) sufficient knowledge, after education 80 (94.11%) or almost all of them had good knowledge. The success of this service activity is due to the support of its main partners in supporting educational facilities and places as well as efforts to mobilize the participation of pregnant women in this activity.